The wonders of language or How to make noises and influence people - Roberts, Ian G. (Cambridge University Press, 2017)
"Ian Roberts offers a stimulating introduction to our greatest gift as a species: our capacity for articulate language. We are mostly as blissfully unaware of the intricacies of the structure of language as fish are of the water they swim in. We live in a mental ocean of nouns, verbs, quantifiers, morphemes, vowels and other rich, strange and deeply fascinating linguistic objects. This book introduces the reader to this amazing world. Offering a thought-provoking and accessible introduction to the main discoveries and theories about language, the book is aimed at general readers and undergraduates who are curious about linguistics and language. Written in a lively and direct style, technical terms are carefully introduced and explained and the book includes a full glossary. The book covers all the central areas of linguistics, including phonetics, phonology, morphology, syntax, semantics and pragmatics, as well as historical linguistics, sociolinguistics and psycholinguistics"--